Development of Learning Media Based on Cross Puzzle Game in Science Learning to Improve Learning Outcomes - Ornella Alika; Elvira Hoesein Radia (Jurnal Penelitian Pendidikan IPA, 2021)
The interest of students in learning Science in Elementary Schools will increase if the teacher uses different learning media than usual. This research and development aim to create a product in the form of science learning media for grade 5 of elementary schools on the material of Animal Classification by the Type of Food as an effort to improve the student-learning outcomes. This study uses the 4D model adapted from the theory of Borg and Gall. This Cross Puzzle Game Media utilizes technology to develop a science-learning media. Two experts who are competent in their fields, namely Material Experts and Media Experts have validated this media. The results of the validation of material results from the media experts reached an average of 3.9 with the valid category, while the material experts got an average of 90% with the very decent category. So that, the assessment results of the Cross Puzzle game are valid and worthy of being used as a learning media to improve the student-learning outcomes.